2015
DOI: 10.1517/14656566.2016.1109629
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of canagliflozin in type 2 diabetes mellitus: systematic review of randomized controlled trials

Abstract: Canagliflozin monotherapy or combination therapy has the potential to decrease inadequately controlled hyperglycemia in T2DM. It acts by a novel insulin independent mechanism which complements the action of the existing AHA and improves glycemic control and decreases the body weight. Safety profile of canagliflozin indicates lower number of hypoglycemic episodes. Some manageable adverse events include genital mycotic infections, urinary tract infections, osmotic diuresis-related events etc. These findings affi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Osmotic diuresis with dapagliflozin was not associated with a significantly increased incidence of events related to volume reduction in a pooled analysis of clinical trials [31], and similar results were reported with empagliflozin [32]. Osmotic diuresis-related events were rare and easily manageable in clinical trials with canagliflozin [33]. Furthermore, no significant reduction of potassium levels was observed in patients with T2D [34], whereas a higher risk of hypokalaemia is commonly observed with HCTZ (Table 1) [35].…”
Section: Diuretic Effects Of Sglt2 Inhibitorssupporting
confidence: 56%
“…Osmotic diuresis with dapagliflozin was not associated with a significantly increased incidence of events related to volume reduction in a pooled analysis of clinical trials [31], and similar results were reported with empagliflozin [32]. Osmotic diuresis-related events were rare and easily manageable in clinical trials with canagliflozin [33]. Furthermore, no significant reduction of potassium levels was observed in patients with T2D [34], whereas a higher risk of hypokalaemia is commonly observed with HCTZ (Table 1) [35].…”
Section: Diuretic Effects Of Sglt2 Inhibitorssupporting
confidence: 56%
“…DM being the most common endocrine disorder with its increasing prevalence every year needs to be addressed urgently (17), as the complications of diabetes may become larger h e a l t h p r o b l e m . A s e v i d e n t b y m a n y epidemiologic studies, most T2DM cases are attributable to modifiable habits and lifestyle factors.…”
Section: Discussionmentioning
confidence: 99%
“…To maintain double-blinding, placebo tablets matched the ertugliflozin 5 mg and 10 mg tablets, and patients were instructed to take two tablets daily of ertugliflozin/placebo. [12][13][14][15][16][17][18]. Participants who received glycemic rescue therapy remained in the study and continued to receive blinded study medication (ertugliflozin or matching placebo) for the duration of the study.…”
Section: Methodsmentioning
confidence: 99%
“…SGLT2 inhibitors represent a class of AHAs that decrease renal glucose reabsorption from the proximal tubule of the kidney, thereby enhancing urinary glucose excretion and reducing plasma glucose and HbA1c [8]. Unlike SUs, SGLT2 inhibitors act independently of beta cell function and insulin sensitivity, are not associated with hypoglycemia when used as monotherapy, and are associated with weight loss [9][10][11][12]. SGLT2 inhibitors have also been demonstrated to have cardiovascular (CV) and renal benefits [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%